Research progress, hotspot analysis, and development trend outlook in the field of digital inclusive finance: A visualization study based on Citespace - Guan, Xuefei; Tantowi, Nur Adeelah Che Ahmad; Samsudin, Shamzaeffa (Edelweiss Applied Science and Technology, 2026)
This study conducts a bibliometric analysis to delineate the intellectual structure and evolutionary trajectory of digital inclusive finance (DIF). Based on a dataset of 850 publications from the Web of Science Core Collection (2017–2025), we utilized CiteSpace 6.4.R1 to perform keyword co-occurrence, clustering, and burst detection analyses. Our findings indicate a rapidly growing body of literature, with China emerging as the leading contributor. Three primary research directions were identified: the theoretical underpinnings of DIF, its economic consequences, and its role in sustainable development. The field’s focus has shifted from foundational concepts to practical impacts, such as alleviating financing constraints and fostering innovation. Currently, scholarly attention is centered on high-quality development, with “efficiency” and “entrepreneurship” being prominent buzz terms. Future research is anticipated to concentrate on “poverty” and “industry.” This paper offers a systematic mapping of the DIF field, providing valuable insights into its current state and future directions. The implications are significant for scholars seeking to identify research gaps and for policymakers aiming to leverage DIF.